(untitled) (Research, Society and Development, 2022)
Probiotics are live microorganisms that beneficially affect the host when administered in adequate amounts, in addition to having an excellent safety profile. For this reason, probiotics have been used as immunomodulators in inflammatory skin diseases such as inflammatory acne. This study aimed to evaluate the therapeutic action of probiotics in acne. An integrative literature review was carried out. Quantitative and qualitative data performed in culture medium and in humans. Electronic searches were performed on PubMed/MEDLINE and BIREME, considering published studies without date limits. The search took place in October 2020, using a combination of the following terms and correlates: “probiotic” and “acne”. Ten studies were included, four in vivo and six in vitro. The studies used several probiotics known in the literature for supplementation, obtaining a positive result. However, there are still few studies that use probiotics to acne treatment as an adjunct with antibiotics or alone.